Contact analysis of a planetary gear train using linear complementarity. (October 2019) - Pathak, M; Rakshit, S
Abstract: The current computation models for gear contact analysis and wear prediction are mostly based on finite element principles which consumes a lot of computation time and effort. In this paper, an alternate approach of linear complementarity is used for gear contact analysis. This approach was successfully applied for a pair of rigid spur gears in our previous paper. In this paper, we are extending this to a planetary gear train. The linear complementarity problem formulation is revised to take bilateral constraints into consideration. A linear complementarity solver computes the contact forces between meshing teeth of gears in gear train. From the contact forces, sliding wear in gear teeth is predicted. Archard's wear model is used for the wear prediction.